Aprepitant versus Olanzapine in Patients of Breast Cancer on Adriamycin and Cyclophosphamide Regimen – Role in Effectiveness of Prevention of Nausea and Vomiting - Sarma, Indrani Devi; Buragohain, Sukainnya; Lahon, Joonmoni; Bhagawati, Indrani; Mahanta, Neelakshi; Saikia, Dibyajyoti (Acta medica Lituanica, 2025)
Background: Chemotherapy-induced nausea and vomiting (CINV) is a significant concern for patients undergoing highly emetogenic chemotherapy (HEC). This study compares the efficacy of aprepitant and olanzapine in preventing CINV in breast cancer patients receiving Adriamycin and Cyclophosphamide (AC).Methods: A prospective, comparative, observational study was conducted over one year at the State Cancer Institute, Guwahati, India. 103 chemotherapy-naïve breast cancer patients were enrolled and divided into two groups: aprepitant and olanzapine, both receiving standard therapy with ondansetron and dexamethasone. CINV outcomes were assessed using the Multinational Association of Supportive Care in Cancer (MASCC) Antiemesis Tool over five days post-chemotherapy. Acute (0–24 hours) and delayed (24–120 hours) nausea and vomiting were evaluated. Side effects were documented and compared between groups.Results: Olanzapine demonstrated significantly better control of acute nausea compared to aprepitant (p < 0.05). It also showed a trend towards superior efficacy in delayed nausea, though statistical significance was not reached. There was no significant difference between aprepitant and olanzapine in preventing acute or delayed vomiting. The olanzapine group experienced more frequent side effects, but the difference was statistically insignificant.Conclusion: Olanzapine exhibited greater efficacy in preventing nausea, particularly in the acute phase, compared to aprepitant. However, its higher side effect profile suggests that careful patient selection is necessary. Both agents remain effective options for CINV management, with olanzapine offering an advantage in nausea prevention.